2005
DOI: 10.1007/s00415-005-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of acute movement disorders

Abstract: Most movement disorders, reflecting degenerative disorders, develop in a slowly progressive fashion. Some movement disorders, however, manifest with an acute onset. We wish to give an overview of the management and therapy of those acute-onset movement disorders.Drug-induced movement disorders are mainly caused by dopamine-receptor blockers (DRB) as used as antipsychotics (neuroleptics) and antiemetics. Acute dystonic reactions usually occur within the first four days of treatment. Typically, cranial pharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 61 publications
0
35
1
2
Order By: Relevance
“…Heat stress has also been clearly shown to trigger fulminant MH in susceptible mice (Chelu et al, 2006;Yang et al, 2006), although its etiological role in human MH and MH in other species is debated (Robinson et al, 2003). Dantrolene is also clinically useful for the treatment of spasticity or muscle spasms associated with several clinical conditions, including spinal cord injuries, stroke, multiple sclerosis, and cerebral palsy (Chou et al, 2004;Dressler and Benecke, 2005;Saulino and Jacobs, 2006;Verrotti et al, 2006). Dantrolene has been used successfully to mitigate symptoms arising from neuroleptic malignant syndrome (Lappa et al, 2002;Strawn et al, 2007), but meta-analysis of 271 case reports has indicated an overall higher mortality rate when dantrolene monotherapy is used to treat neuroleptic malignant syndrome (Reulbach et al, 2007).…”
mentioning
confidence: 99%
“…Heat stress has also been clearly shown to trigger fulminant MH in susceptible mice (Chelu et al, 2006;Yang et al, 2006), although its etiological role in human MH and MH in other species is debated (Robinson et al, 2003). Dantrolene is also clinically useful for the treatment of spasticity or muscle spasms associated with several clinical conditions, including spinal cord injuries, stroke, multiple sclerosis, and cerebral palsy (Chou et al, 2004;Dressler and Benecke, 2005;Saulino and Jacobs, 2006;Verrotti et al, 2006). Dantrolene has been used successfully to mitigate symptoms arising from neuroleptic malignant syndrome (Lappa et al, 2002;Strawn et al, 2007), but meta-analysis of 271 case reports has indicated an overall higher mortality rate when dantrolene monotherapy is used to treat neuroleptic malignant syndrome (Reulbach et al, 2007).…”
mentioning
confidence: 99%
“…We had chosen to treat her putative movement disorder with phenytoin due to its potency and efficacy in a variety of paroxysmal movement disorders. 6 Carbamazepine might also have been effective but lacks a readily available IV preparation. Her immediate and complete response to phenytoin, coupled with the MRI localization to the area of her motor cortex controlling the face, argued that these movements were in fact seizures.…”
Section: Sectionmentioning
confidence: 99%
“…Movements vary from fleeting disturbance to maintained abnormal postures [15]. It may occur in 25% to 40% of patients receiving typical antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…It includes 50% of extrapyramidal symptoms and is considered one of the most common movement disorders caused by antipsychotics [18]. Akathisia may also be caused by antiemetics, serotonergic agents, serotonin reuptake inhibitors and cocaine [19]. The patients suffer from the feeling of restlessness and an irresistible urge to move.…”
Section: Introductionmentioning
confidence: 99%